2000
DOI: 10.1034/j.1600-0706.2000.900114.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of habitat structure to the arthropod food‐web in Douglas‐fir canopies

Abstract: 2000. Importance of habitat structure to the arthropod food-web in Douglas-fir canopies. -Oikos 90: 139 -152.This study tested the hypothesis that habitat structure dictates the distribution and community composition of arboreal arthropods. A diverse arthropod assemblage of Douglas-fir canopies, which included Araneae, Psocoptera, Collembola and Homoptera, was chosen as a model system. Habitat structural diversity, defined as needle density and branching complexity of Douglas-fir branches, was manipulated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
191
2
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(218 citation statements)
references
References 52 publications
(64 reference statements)
12
191
2
8
Order By: Relevance
“…The highest predation rate at the forest interior supports the assumption that abundance of predators also declines with increasing forest fragmentation and isolation [2]. Such findings are in agreement with outcomes of pitfall trap studies, which confirm positive correlations between low canopy openness and predation activity [19][20][21][22]. Differences between forest edge and interior in predation rate recorded in our experiments probably result from temperature variability within and between the two habitats.…”
Section: Effect Of Canopy Openness In Forest and Non-forest Habitats supporting
confidence: 81%
See 1 more Smart Citation
“…The highest predation rate at the forest interior supports the assumption that abundance of predators also declines with increasing forest fragmentation and isolation [2]. Such findings are in agreement with outcomes of pitfall trap studies, which confirm positive correlations between low canopy openness and predation activity [19][20][21][22]. Differences between forest edge and interior in predation rate recorded in our experiments probably result from temperature variability within and between the two habitats.…”
Section: Effect Of Canopy Openness In Forest and Non-forest Habitats supporting
confidence: 81%
“…Generally, we can say that litter affects predator abundances through at least four mechanisms: (1) access to alternative prey; (2) reduction of interspecific competition and prevention of intraguild predation [9]; (3) provision of overwintering sites, places for reproduction, and shelters to hide from higher trophic level predators [13][14][15]; and (4) reduction of abiotic stressors [6,9,[16][17][18]. The use of pitfall trapping to study activity of predators has confirmed that vegetation density positively correlates with activity and abundance of predators [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…species that are specifically adapted for living in forest habitats). Spiders are generalist predators and are more dependent on habitat structure and prey availability than the actual species of tree which they inhabit (Halaj et al 1998(Halaj et al , 2000Purchart et al 2013). By contrast the species richness of canopy-dwelling beetles was consistently higher in oak and ash woodlands than in forest plantations.…”
Section: Species Diversitymentioning
confidence: 99%
“…Estes organismos caracterizam-se por não apresentarem especificidade hospedeira e por sua distribuição depender, diretamente, da estrutura física do ambiente e da disponibilidade de presas na área (Halaj et al 2000, Sørensen 2003, fornecendo, assim, informações precisas sobre a estrutura de habitats, composição e organização das comunidades de invertebrados terrestres (Silva & Coddington 1996).…”
Section: Introductionunclassified